Sistem Informasi Pinjaman Dana Tunai Berbasis Web Dengan Mengggunakan Database MySQL - Muhammad Makmun Effendi (Teknik Informatika, Universitas Pelita Bangsa, 2021)
The information system of cash loans aim to help facilitate in obtaining information quickly and accurately. Is expected to provide a number of benefits and usefulness both for writers and companies. The research methodology used includes the step of collecting data is a literature study, observation, interview and stage of manufacture of such systems, analysis, design, coding, testing, maintenance. Results from this study that in order to establish a reliable information system needed an information system that is accurate and supported by the ability of adequate human resources. It is necessary for the construction of an information system in real time based technology kumputer. Keywords: Systems, Information Systems, Cash Loans, Database, UML.